Children Deprived of Parental Care and Protecting Their Interests - Feruzaxon, Turaboyeva (Research Parks Publishers, 2023)
today among the categories of the population in need of special care - orphans and children left without parental care occupy a special place. The main task of society is to educate children as full - fledged healthy-thinking citizens, able to adapt to collective life and instill in them both professional and various life skills in their subsequent getting used to social situations.